Manajemen UIN Sunan Kalijaga Yogyakarta Dalam Akreditasi FIBAA Tahun 2022 - Rika Evania Muslimatun; Zainal Arifin; Nora Saiva Jannana; Sedya Santosa (STAI Terpadu Yogyakarta, 2023)
This study aims to determine international accreditation management to assess quality standards at UIN Sunan Kalijaga. The research method used is descriptive qualitative. The results showed that UIN Sunan Kalijaga has implemented an international standard quality assurance system and has received FIBAA international accreditation and AUN-QA certification. In 4ICU Unirank 2022 UIN Sunan Kalijaga obtained the top 16 rankings of the best Islamic universities in the world and the best Islamic universities nationwide.